In vitro Seed Germination and Shoot Multiplication of Seven Endemic Subalpine and Alpine Plant Species Grown on Mount Jaya, Papua, Indonesia - Ermayanti, Tri Muji; Hafiizh, Erwin Al; Mandessy, Ary; Setyadi, Gesang; Mukhsia, Andi (BRIN, 2014)
Exploitation on plant population may put the endemic plants into an endangered state, hence, these plants will need to be conserved. In order to pursue conservation on endemic plants, we conducted in vitro seed germination and shoot multiplication of seven alpine and sub-alpine species endemic to Mount (Mt.) Jaya, in Papua, Indonesia, i.e. Tetramolopium klossii, Deschampsia klossii, Papuacalia cartenszensis, Epilobium hooglandii, Gaultheria novoguinensis, Rhododendron correoides, and Rhododendron culminicolum. These species are categorized as slow-growth plants found in higher altitude (over 3700 m above sea level) and low temperature of Mt. Jaya. Seeds were surface-sterilized using Na-hypochloride and germinated aseptically on Murashige and Skoog (MS) medium. Dytikinin benzyl adenine (BA) was used for shoot multiplication. Seedling cultures were maintained in a controlled environment with continuous low light intensity (800 lux) and at temperature 26-27oC. Results showed that most species had more than 80% of germination rate on MS medium after a week in culture. BA was required to enhance shoots multiplication. Woody Plant (WP) (Lloyd & McCown, 1981) medium gave better shoot multiplication for R. culminicolum.